European liberalisms: an essay in comparative political thought - Freeden, M (SAGE Publications, 2008)
After examining different liberal narratives and suggesting that liberalism is open to a range of legitimate methodologies, the fluidity of liberalism is offered as a basis for a study in comparative political thought. Ten propositions on liberalism's structural and semantic features are listed and brought to bear on its adaptations, appropriations and misappropriations in Europe. They are tested in relation to various combinations of liberal components within and outside the family of liberalisms. Different views about the role of the state in Eastern and Western Europe are considered, as is the distinction between constitutional and welfare liberalism in Western Europe. Individual development versions are contrasted with market versions, and the problematic role of civil society is discussed. Finally, some misappropriations are explored with a view to assessing their claims to represent liberal positions. European liberalism emerges as a loosely assembled yet durable ideology around a strong core of value-commitments.